The Role of Digital Marketing in International Marketing - Lubis, Etrie Septiani; Widodo, Slamet (Yayasan Sinergi Kawula Muda, 2024)
This research explores the role of digital marketing in international marketing, focusing on effective strategies, challenges, and methods of measuring success. Using a qualitative approach with literature studies from credible sources such as scientific journals, news articles, and official company websites, the data was analyzed descriptively qualitatively. The results show that digital marketing allows companies to reach global audiences more efficiently through SEO, social media, email marketing, and PPC. Challenges faced include differences in culture, language, regulations, and consumer preferences. Effective strategies include locally relevant content, appropriate use of social media platforms, and in-depth data analysis. This research provides insight for business practitioners in developing effective digital marketing strategies to improve performance in various countries.